A Guideline for The Environmentally Friendly Port Management and The Artisanal Fisheries Community Rights in the Eastern Economic Corridor Project: A Case Study of Chonburi Province - Sungkaew, Buchita; Kanjanawong, Danusorn; Dongjit, Jatupon (King Prajadhipok’s Institute Journal, 2021)
The environmentally friendly port management and the promotion of artisanal-fishery community rights to participate in marine environmental management are both a significant concept and guideline for sustainable development. This article aims to disseminate knowledge about environmental-friendly port management and the promotion of artisanal-fishery community rights towards marine environmental management which will lead to sustainable development in terms of economy, environment and society in the Eastern Economic Corridor Project, Chonburi Province. It focuses on explaining the relationships among environmental-friendly port management, the promotion of artisanal-fishery community rights, and sustainable development in marine environment. Moreover, it would point out the spatial-problem issue, and the proposal for the promotion of artisanal-fishery community rights in order to make environmental-friendly port management consistent with the development principles of international port standards. Thus, a case study of Chonburi province was presented in this article as a reflection of the spatial problem from the economic-development activities in the port which had an impact on environment and artisanal-fishery community rights, so port authority should be promotion of artisanal-fishery community rights guideline established in order to reach an environmental-friendly port and sustainable development. It should be done through the development of policy and law, the cooperation of marine-environmental-network models between the port and the community, as well as an encouragement to establish artisanal-fishery community funds for sustainable marine-environmental management.